Strophomenata (Brachiopoda) in Devonian deposits from the State of Paraná, Brazil: a case study (Terr@ Plural, 2023)
Strophomenata (Rhynchonelliformea brachiopods) are extinct and presumably confined to the Paleozoic. The class comprises the orders Strophomenida, Productida, Orthotetida, and Billingsellida. Three of these four orders have representatives in Brazilian Paleozoic sediments: Strophomenida (Superfamily Strophomenoidea), Orthotetida (Suborder Orthotetidina), and Productida (suborders Chonetidina and Productina). Therefore, we carried out a bibliographic survey and a taphonomic analysis of the occurrence mode of the class in Devonian sedimentary deposits of the Paraná Basin, in the state of Paraná. It was formally recognized Strophomenids representing the orders Productida (Suborder Chonetidina) and Orthotetida (Suborder Orthotetidina), both being present in the Ponta Grossa and São Domingos formations. It was identified six different occurrences suggesting that strophomenids might be a potential bioindicator of bathymetric gradients.
Keywords: Rhynchonelliformea, Ponta Grossa Formation, São Domingos Formation, Devonian, Taphonomy.